THE INFLUENCE OF FINANCIAL SUPPORT, EDUCATIONAL MOTIVATION, AND FAMILY SUPPORT ON TIMELY GRADUATION FOR STUDENTS RECEIVING THE INDONESIA SMART CARD SCHOLARSHIP (KIP-K) - Bambang Yudi Permana; Didik Hariyadi Raharjo (RADJA PUBLIKA, 2025)
This study investigates how students receiving the Indonesia Smart Card Scholarship (KIP-K) Program D4 in DKI Jakarta have the influence of financial support, educational motivation, and family support on timely graduation. Data were collected using a quantitative survey design and quantitative approach. Questionnaires were distributed to 31 respondents and analyzed using multiple linear regression. Validity, reliability, and classical assumptions such as normality, multicollinearity, and heteroscedasticity tests were the analysis tools. The results showed that all three variables, both partially and simultaneously, had a significant effect on timely graduation. Students have found that getting financial support helps them reduce the stress associated with their education costs. In addition, family support helps students maintain their academic spirit, and increases their academic motivation. It is expected that these findings will provide insight strategic for the development of scholarship policies and increasing the effectiveness of the KIP-K program in Indonesia.